Company Group Affiliations and Corporate Bond Yield Spread: Study Non-financial Companies - Dwita Purwanti (Syntax Literate, 2023)
This study examines the impact of corporate groups on corporate bond yield. The results of the study indicate whether related groups issue bonds with higher yield spreads than independent companies. In Indonesia, research is still limited to further analyse the impact of corporate groups, in particular, on bond yields. In this study, the study period was taken from non-financial services corporate bond issuances from 2013 to 2022, and a total of 328 series of conventional bonds from 48 non-financial services corporate and bank issuers were used.